The Danish Fetal Medicine Database: establishment, organization and quality assessment of the first trimester screening program for trisomy 21 in Denmark 2008–2012. (24th February 2015) - Ekelund, Charlotte K.; Petersen, Olav B.; Jørgensen, Finn S.; Kjaergaard, Susanne; Larsen, Torben; Olesen, Annette W.; Skibsted, Lillian; Skovbo, Peter; Sommer, Steffen; Sperling, Lene; Stavnstrup, Benedicte; Størup, Birgitte; et al.
Abstract Objective To describe the establishment and organization of the Danish Fetal Medicine Database and to report national results of first‐trimester combined screening for trisomy 21 in the 5‐year period 2008–2012. Design National register study using prospectively collected first‐trimester screening data from the Danish Fetal Medicine Database. Population Pregnant women in Denmark undergoing first‐trimester screening for trisomy 21. Methods Data on maternal characteristics, biochemical and ultrasonic markers are continuously sent electronically from local fetal medicine databases (Astraia Gmbh software) to a central national database. Data are linked to outcome data from the National Birth Register, the National Patient Register and the National Cytogenetic Register via the mother's unique personal registration number. First‐trimester screening data from 2008 to 2012 were retrieved. Main outcome measures Screening performance was assessed for the years 2008–2012 by calculating detection rates and screen‐positive rates. Results A total of 268 342 first‐trimester risk assessments for trisomy 21 were performed in singleton pregnancies. Participation rate in first‐trimester screening was >90%. The national screen‐positive rate increased from 3.6% in 2008 to 4.7% in 2012. The national detection rate of trisomy 21 was reported to be between 82 and 90% in the 5‐year period. Conclusion A national fetal medicine database has been successfully established in Denmark. Results from the database have shown that at a national level first‐trimester screening performance for trisomy 21 is high with a low screen‐positive rate and a high detection rate.